Counter ions and constituents combination affect DODAX : MO nanocarriers toxicity in vitro and in vivo. Issue 4 (13th June 2016) - Oliveira, Ana Cristina Norberto; Sárria, Marisa Passos; Moreira, Pedro; Fernandes, Joana; Castro, Lisandra; Lopes, Ivo; Côrte-Real, Manuela; Cavaco-Paulo, Artur; Real Oliveira, Maria Elisabete Cunha Dias; Gomes, Andreia Castro
Abstract : To accurately evaluate harmful effects on cells, tissues and organisms, DODAX : MO liposomes were evaluated in vitro and in vivo . Toxicity was found to depend on counter-ions and helper lipid contents. Abstract : Liposomes have received extensive attention as nanocarriers for bioactive compounds due to their good biocompatibility, possibility of targeting and incorporation of hydrophilic and hydrophobic compounds. Although generally considered as safe, detailed knowledge of the effects induced in cells and tissues with which they interact is still underexplored. The aim of this study is to gain insight into the toxicity profile of dioctadecyldimethylammonium (DODAX) : monoolein(MO) liposomes (X is bromide or chloride), previously validated for gene therapy, by evaluating the effect of the counter ions Br − or Cl −, and of the cationic : neutral lipid molar fraction, both in vitro and in vivo . Effects on cellular metabolism and proliferation, plasma membrane integrity, oxidative stress, mitochondrial membrane potential dysfunction and ability to trigger apoptosis and necrosis were evaluated in a dose-/time-dependent manner in normal human skin fibroblasts. Also, newly fertilized zebrafish zygotes were exposed to liposomes, permitting a fast-track evaluation of the morphophysiological modifications. In vitro data showed that only very high doses of DODAX : MO induce apoptosis and necrosis, inhibit cell proliferation, and affect the metabolism and plasma membrane integrity of fibroblasts in a dose-/time-dependent manner. Furthermore, liposomes affected mitochondrial function, increasing ROS accumulation and disturbing mitochondrial membrane potential. DODAC-based liposomes were consistently more toxic when compared to DODAB-based formulations; furthermore, the inclusion of MO was found to reduce toxicity, in contrast to liposomes with cationic DODAX only, especially in DODAB : MO (1 : 2) nanocarriers. These results were corroborated, in a holistic approach, by cytotoxicity profiling in five additional human cell lines, and also with the zebrafish embryotoxicity testing, which constitutes a sensitive and informative tool and accurately extends cell-based assays.